Clay roofing tiles under salt mist atmosphere - Cruz, C. (2012)
A research is being carried out to study the degradation of clay roofing tiles subjected to sea environment. Some case studies are analyzed and their state of conservation is evaluated. The program comprises artificial weathering tests of exposition to salt mist of different kinds of clay tiles currently used, as well as natural weathering tests in controlled conditions. The weathering effect is monitored in both situations, through visual analysis and physical tests followed by comparison of the results. The kind and severity of degradation obtained by the weathering tests are compared with the problems observed in the case studies with a view to provide information about the degradation mechanisms and the factors involved. In this paper some of the results obtained so far are presented. Some case studies of natural damage of roofing tiles on the central coast of Portugal are analyzed, considering environmental and exposition conditions. Artificial accelerated tests are described and their visual inspection results are presented and compared with those of the natural damage cases. Finally, natural exposition tests installation is described.